The Claim Over Sabah by the Sultanate of Sulu: A Revision from Historical and Legal Perspectives - Aziz, Hamdan; Said, Syahrin (Melayu: Jurnal Antarabangsa Dunia Melayu, 2016)
This paper aims to discuss the debate regarding the demands of the heirs of the Sultanate of Sulu (Philippines) on Sabah from historical and legal perspectives. These have recently resurfaced due to the Lahad Datu incident triggered by the Royal Army of Sulu, who attempted to reclaim Sabah (North Borneo) in mid-February 2013. The fundamental question in dispute is whether was Sabah leased by the Sultanate of Sulu to the British North Borneo Chartered Company, or leased to it in perpetuity. The dispute dates back to 1878, when Overbeck entered into an agreement with Sultan of Sulu to occupy Sabah with an annual payment of $5000 per year. Based on the elements of effectiveness that have been taken into account by the International Court of Justice in the case of overlapping claims on Pulau Sipadan-Ligitan, which awarded it to Malaysia and not Indonesia, Sabah belongs to Malaysia. Several statements from protocols, agreements, declarations and the constitution confirm that Sabah was leased in perpetuity. Keywords: territorial claims, Sabah, Sulu, disputes, lease in perpetuity